1994
DOI: 10.1530/jrf.0.1020393
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for testicular macrophages in Leydig cell proliferation and differentiation during prepubertal development in rats

Abstract: Testicular macrophages in rats were selectively depleted by an intratesticular injection of liposomes containing dichloromethylene diphosphonate into the right testis to study the possible role of these macrophages during the prepubertal development of Leydig cells. The contralateral testes were injected with 0.9% NaCl and served as controls. The animals were injected with the liposomes and NaCl at 5, 10, 15, 20 or 25 days of age. In macrophage-depleted testes, Leydig cell development was inhibited in the anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 2 publications
5
63
0
Order By: Relevance
“…It remains possible, nevertheless, that changes in ALC differentiation may have been affected by altered macrophage numbers. Previous studies have suggested that macrophages generally enhance LC function and development (Chen et al, 2002;Gaytan et al, 1994), although activation of macrophage invasion can have an inhibitory effect (Hales, 2002). In this case, it appears unlikely that the marked reduction in ALC development following SC ablation is caused by the transient increase in macrophage numbers for the following three reasons.…”
Section: Discussionmentioning
confidence: 83%
“…It remains possible, nevertheless, that changes in ALC differentiation may have been affected by altered macrophage numbers. Previous studies have suggested that macrophages generally enhance LC function and development (Chen et al, 2002;Gaytan et al, 1994), although activation of macrophage invasion can have an inhibitory effect (Hales, 2002). In this case, it appears unlikely that the marked reduction in ALC development following SC ablation is caused by the transient increase in macrophage numbers for the following three reasons.…”
Section: Discussionmentioning
confidence: 83%
“…Testicular macrophages play an integral role in the interstitial tissue of the rat testis and secrete a number of cytokines, some of which are mitogenic to Leydig cells (Gaytan et al, 1994;Hutson, 1994). Impaired macrophage function leads to delayed or absent Leydig cell development, as supported by a model in which macrophages were depleted from the neonatal testis.…”
Section: Regulation Of Leydig Cells By Hormones and Local Growth Factorsmentioning
confidence: 97%
“…In the postnatal and adult testis, macrophages make up a large portion of the interstitial compartment (20) and are important for Leydig cell development and steroidogenic function (21,22). However, macrophages have not been detected or functionally characterized during fetal testis morphogenesis.…”
mentioning
confidence: 99%